PERCEPATAN ADOPSI SISTEM TRANSAKSI TEKNOLOGI INFORMASI UNTUK MENINGKATKAN AKSESIBILITAS LAYANAN JASA PERBANKAN - Ikaputera Waspada (University of Merdeka Malang, 2012)
E-money had potential as an effective transaction payment tool especially for micro transactions, but publicadoption level was relatively low. The research object was to find the factors that influenced the acceptance levelof e-Money in customer and business user, to develop an acceleration of adoption strategy of e-Money in thepublic. The research methods used in this research were Descriptive and Verificative methods. The respondentsconsisted of customer and business user in Bandung. The sample was chosen purposively. The respondentsfrom business user shown that e-money performance which considered good was transaction speed, easiness toturn into cash, operational easiness and low transaction cost.